Tax and credit aids to industrial development in Southern Italy. Reply to comment by Dr. Kauffman - ACKLEY, G.; DINI, L. (PSL Quarterly Review, 2014)
In this brief note, the authors respond K.M. Kauffman’s comment on the methodology used in their article “Tax and Credit Aids to Industrial Development in Southern Italy”. It is argued that Kauffman’s “correct method” still involves certain difficulties. The recognition of such was among the reasons why the authors chose their simplified approximation to begin with. JEL: H25, H81, O14, O18